Current Status of mCRC in East Europe and Middle East. - Yazici, Ozan; Ucar, Gokhan; Vasileia, Vamvakopoulou; Turhal, Serdar Nazim; Yildiz, Birol; Karamouzis, Michalis; Yavuz, Sinan; Karadurmus, Nuri; Zengin, Nurullah; Abali, Huseyin; Geva, Ravit (LIPPINCOTT WILLIAMS \& WILKINS, 2018)
Gastrointestinal Cancers Symposium of the American-Society-of-Clinical-Oncology (ASCO), San Francisco, CA, JAN 18-20, 2018